S-WAVE SPECTRAL ANALYSIS AND ESTIMATION OF SPECTRAL PARAMETERS IN NORTHWESTERN GREECE - Stavroulopoulou, O.; Sokos, E.; Tselentis, G.A. (Bulletin of the Geological Society of Greece, 2016)
During a 12-month period (August 1998 - June 1999), a dense microseismic network of 44 portable seismographs, was installed in Epirus - Northwestern Greece, by the Seismological Laboratory, of the University of Patras and recorded 1368 earthquakes. We selected a subset of 200 well recorded events, with duration magnitude ranging from 1.61 to 2.92 and focal depths ranging from a few hundred meters to 35km; the majority was in the 0-10km range. This study uses this high quality dataset to (i)calculate the earthquake spectra and source parameters; (ii) perform linear regression between Seismic Moment (M0) and the source parameters Source Radius (r), Stress Drop (Δσ) and Displacement (s); (iii) correlate source parameter’s distribution with the tectonics of the area. Finally, we compare the derived empirical laws with similar studies.